The Influence of Different Concentrations of Isolated Soy Protein (ISP) Powder in Rice Bran Suspension as Feed on the Production of Artemia salina Cysts - Marwah Sifa Safira Mosyafwa; Ahmad Shofy Mubarak; Laksmi Sulmartiwi (Airlangga University, 2025)
Artemia salina is a natural food source known for its high nutritional quality. It is commonly used in larval rearing due to its ability to produce long-lasting cysts that can hatch at any time. These characteristics make A. salina very suitable for sustainable cultivation. In this study, the feed consisted of rice bran suspension enriched with Isolated Soy Protein (ISP) meal. The aim was to investigate the effect of different protein concentrations in the rice bran suspension feed on cyst production in A. salina broodstock. This study used a Completely Randomized Design (CRD) with five treatments and four replications. The treatments included P0 (without ISP meal, 25% protein concentration), P1 (ISP meal, 40% protein concentration), P2 (ISP meal, 45% protein concentration), P3 (ISP meal, 50% protein concentration), and P4 (ISP meal, 55% protein concentration). Data analysis was performed using ANOVA followed by Duncan's multiple range test. The results showed that variations in protein concentration with the addition of ISP flour had a significant effect (P < 0.05) on total cyst production and cyst production per broodstock of A. salina. The highest total cyst production (710.67 cysts/L) was achieved in P4 with a protein concentration of 55%, while the highest cyst production per broodstock (28.67 cysts/broodstock) occurred in P2 with a protein concentration of 45%.